Metastatic Renal Cell Carcinoma in an Ovarian Benign Mixed Mucinous Cystadenoma and Brenner Tumour: A Case Report - Amar Ibrahim; Mohammad Salih Al-Jafari (Case Reports in Pathology)
This is a case of a 71-year-old woman, who presented with a large abdominal mass. Microscopic examination revealed metastatic renal cell carcinoma in an otherwise massively enlarged benign ovarian tumour of mixed mucinous cystadenoma and Brenner tumour. Clinicopathological and radiological assessment together with a thorough evaluation of gross and histological features, including the use of immunohistochemical stains, is essential to confirm the diagnosis and rule out the possibility of primary clear cell carcinoma of ovary, as this has important prognostic and therapeutic implications.